Effects of stand age on community composition and diversity of soil bacteria and fungi in poplar plantations in Northeast China - Zhao, Lei; Mao, Bing; Wang, Hongxing; Jiang, Luping; Huang, Jin; Pang, Zhongyi; Peng, Yanhui; Qu, Tongbao; Zhao, Xiyang (Frontiers in Plant Science, 2025)
Stand age is one of the most important indicators of plantation development status after afforestation. Soil microbial community plays an essential role in ecosystem functioning. Yet, the responses of soil microbial community composition and diversity to stand development are inadequately understood. Here, we examined changes in community composition and diversity of soil bacteria and fungi in poplar plantations across stand ages and their relationships with soil chemical and biochemical properties in Northeast China. We measured soil chemical properties (organic carbon, total nitrogen, total phosphorus and their stoichiometries), soil biochemical properties (microbial biomass, soil enzyme activity and their stoichiometries), and composition and diversity of soil bacterial and fungal communities in a chronosequence (1, 4, 7 and 9 years) of poplar plantations. Furthermore, we analyzed microbial co-occurrence network and the relationships of soil bacterial and fungal community diversity and composition with soil chemical and biochemical properties. The Chao1 index of soil bacteria was lowest in the 9-year-old plantation, and Chao1 index of soil fungi was lowest in the 7-year-old plantation. Soil bacterial and fungal diversity showed a significant relationship with soil microbial biomass. The most dominant bacterial species were from Proteobacteria, Acidobacteriota, Actinobacteriota, Firmicutes and Chloroflexi, and fungal species were from Ascomycota, Basidiomycota and Mortierellomycota. The number of links and average degree of bacterial communities decreased as stand age of poplar plantations increased, while those of fungal communities increased. Soil bacterial and fungal network parameters showed significant relationship with soil microbial biomass ang microbial stoichiometry. Our results showed that the impact of stand age on soil microbial community diversity and composition is specific and stage-dependent, rather than following a simple linear trend with increasing age, and this may be due to the influence of stand age on stoichiometry of soil microbial biomass.